Etnomatematik Melayu - Shaharir Mohamad Zain, (Universiti Kebangsaan Malaysia, 2002)
The mathematics inherited from Malay civilization is still being taught, spoken, written, used and developed in the Malay language, according to the Malay and Islamic values. It is generally known as ethnomathemactics. This type of mathematics consists of Malay indigenous mathematical and human elements that are derived from Islamic values. The definition for this mathematics or the ‘convert’ and its need in the Malay world called pascabima is discussed. The writer attempts to explain a few examples of this type of mathematics that he hopes to develop, besides discussing several wide ranging and concrete issues pertaining to it. It is perceived that it has the potential for further development from the Malay perspective